Telomere Biology and Telomere Diseases: Implications for Practice and Research - Young, Neal S. (Hematology Am Soc Hematol Educ Program, 2010)
The recent recognition of genetic defects in telomeres and telomere repair in multiple human diseases has practical implications for hematologists and oncologists and their patients; consequences for future clinical research in hematology and other subspecialties; and even importance in the interpretation of animal experiments involving cell propagation. Telomere diseases include constitutional marrow failure as dyskeratosis congenita, some apparently acquired aplastic anemia, myelodysplasia and acute myeloid leukemia; pulmonary fibrosis; and hepatic nodular regenerative hyperplasia and cirrhosis. Accelerated telomere attrition is a likely pathophysiology of cancer arising from chronic inflammation. Telomerase can be modulated by sex hormones, which may explain the activity of androgens in marrow failure. Measurement of telomere length of peripheral blood leukocytes is a simple screening clinical assay. Detection of a mutation in a patient has implications for therapy, prognosis, monitoring, and genetic counseling. For research in hematology and oncology, telomere biology could be assessed as a risk for secondary malignancies and in graft-versus-host disease, for progression in a variety of blood cancers, and as potentially modifiable by hormone replacement strategies.